A comparative study of whole genome amplification and low-template DNA profiling. Issue 1 (December 2019) - Han Lim, Hong; Srisiri, Korapin; Rerkamnuaychoke, Budsaba; Bandhaya, Achirapa
Abstract: Generation of high-quality STR profiles from trace amounts of cells remains challenging. Although increasing the number of PCR cycles improves the sensitivity of STR analysis, stochastic effects may complicate interpretation and deem the profiles inconclusive. Whole Genome Amplification (WGA) has been successfully employed to improve the outcome of subsequent STR analysis by increasing the number of available DNA template. However, there is limited information on how WGA performs in comparison to the elevated PCR cycles. This study aims to evaluate the quality of STR profiles obtained from 10 and 25 pg of DNA that had undergone WGA, against that from 32-PCR cycle protocol. Buccal cell DNA was subjected to 16-h WGA using REPLI-g® Single Cell Kit followed by 28-cycle STR amplification with AmpFLSTR™ Identifiler™ Plus PCR Amplification Kit. The results showed that the WGA yielded significantly lower allele detection rates than the 32-cycle PCRs, although the mean peak height ratios were comparable. Few allelic drop-ins were also observed in profiles derived from the WGA products, while none was present in the 32-cycle PCR profiles. These preliminary data suggested that the WGA protocol examined did not offer any improvement on DNA profile quality over the elevated PCR cycle method. However, the success rates of the WGA in this study seemed to contradict the previous reports, thus modifications to the protocol used would be further investigated.